Synthesis, Structure and Antioxidant Properties of Nickel(II) Complex with bis(Benzimidazol-2-ylmethyl)allylamine - Fan, Xuyang; Wang, Xiaoli; Zhang, Jiawen; Chen, Chengyong; Yang, Zaihui; Wu, Huilu (Asian Journal of Chemistry, 2015)
A complex of nickel(II) picrate (pic) with bis(benzimidazol-2-ylmethyl)allylamine (AIDB), with composition [Ni(AIDB)2(pic)2], was synthesized in high yields and characterized by elemental analyses, molar conductivities, UV-visible spectra and IR spectra. X-ray crystallographic investigation of Ni(II) complex is distorted octahedral coordination geometry. The antioxidant activity of the complex was determined by the superoxide and hydroxyl radical scavenging methods in vitro, which indicate that it is a scavenger for OH• and O2–• radicals.